Tumorigenic Properties of Drosophila Epithelial Cells Mutant for lethal giant larvae. Issue 8 (15th July 2016) - Calleja, Manuel; Morata, Ginés; Casanova, Jordi
Abstract : Background: Mutations in Drosophila tumor suppressor genes (TSGs) lead to the formation of invasive tumors in the brain and imaginal discs.Results: Here we studied the tumorigenic properties of imaginal discs mutant for the TSG gene lethal giant larvae ( lgl ). lgl mutant cells display the characteristic features of mammalian tumor cells: they can proliferate indefinitely, induce additional tracheogenesis (an insect counterpart of vasculogenesis) and invade neighboring tissues. Lgl mutant tissues exhibit high apoptotic levels, which lead to the activation of the Jun‐N‐Terminal Kinase (JNK) pathway. We propose that JNK is a key factor in the acquisition of these tumorigenic properties; it promotes cell proliferation and induces high levels of Mmp1 and confers tumor cells capacity to invade wild‐type tissue. Noteworthy, lgl RNAi‐mediated down‐regulation does not produce similar transformations in the central nervous system (CNS), thereby indicating a fundamental difference between the cells of developing imaginal discs and those of differentiated organs. We discuss these results in the light of the "single big‐hit origin" of some human pediatric or developmental cancers.Conclusions: Down‐regulation of lgl in imaginal discs is sufficient to enhance tracheogenesis and to promote invasion and colonization of other larval structures including the CNS. Developmental Dynamics 245:834–843, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: Imaginal discs mutant for the lethal giant larvae (lgl) gene fuse together and form massive overgrowths that contain supernumerary trachea. During the fusion process some epithelial cells change their identity to become tracheal cells. Igl mutant discs exhibit high levels of apoptosis and of ectopic Jun‐N Terminal Kinase (JNK) activity. In these discs, the activity of JNK induces high levels of Metalloprotease that in turn induce additional tracheogenesis and facilitate the fusion of different discs.